Poverty impacts of food price increases in Niger - Minot, Nicholas; Martin, Will (International Food Policy Research Institute, 2023)
The prices of staple grains began rising in mid-2020, reflecting higher fertilizer prices and the supply chain bottlenecks caused by the outbreak of Covid-19, and increased sharply following the Russian invasion of Ukraine in early 2022. How have these dramatic increases in world prices of cereals affected poverty in low-income countries? This brief estimates the impact of higher world grain prices on poverty in Niger. Other briefs in this series examine the impact of higher food prices on poverty in Kenya, Ethiopia, Nigeria, Burkina Faso, and Mali (see Minot and Martin, 2023a and 2023b; Martin and Minot, 2023a, 2023b, and 2023c). All six studies use a similar approach. First, we examine the effect of the rise in international cereal prices on the real price of key grains in the domestic markets of the country. Second, we estimate the impact of the changes in domestic grain prices on the real income of each household using nationally-representative survey data, taking into account the importance of the commodities in consumption and as a source of income for each household. Finally, we estimate the changes in headcount poverty (the share of people living below the poverty line) based on the changes in real income for each household in the sample. We focus on the prices of maize, wheat, and sorghum for reasons discussed below.